Long‐Term Peak Geoelectric Field Behavior for Space Weather Hazard Assessment in Alberta, Canada Using Geomagnetic and Magnetotelluric Measurements - Darcy Cordell; Ian R. Mann; Stavros Dimitrakoudis; Hannah Parry; Martyn J. Unsworth (Space Weather)
Abstract To better understand the risks of space weather to electric power transmission networks, magnetometer data and nearby magnetotelluric impedance data at four sites in Alberta, Canada are used to estimate the induced geoelectric field over the last 12–32 years. Peak geoelectric fields >11 and ∼1 V/km are estimated in northern and southern Alberta, respectively. Peak magnitudes decrease from north to south partially due to magnetic latitude, but primarily due to variations in ground conductivity, highlighting the importance of including realistic geological information. Best estimates of 1‐in‐100 years return levels range from 2.0 to 9.2 V/km in southern and northern Alberta, respectively, exceeding 8 V/km NERC benchmarks in some cases. Large geoelectric fields can occur any time of day, although they are more likely during nightside events and on the dawn flank. Events that exceed 1 V/km can last >8 min which warrants further investigation since these events may cause more damaging GIC due to extended periods of transformer heating. The rate of change of the horizontal magnetic field (dbh/dt) is not particularly well‐correlated with the geoelectric field (0.4 < R < 0.7), suggesting that dbh/dt may not always represent a good proxy for risk to the power network. The ground impedance partially explains these poor correlations; regions with a resistive surface layer (northern Alberta) have better correlations with dbh/dt than regions with a conductive surface layer (southern Alberta) because the shallow conductor filters high frequency components of the geoelectric field which are present in the dbh/dt time series.